"Banishing the atom pile bogy": Exhibiting Britain's first nuclear reactor. (18th February 2020) - Boyle, Alison
Abstract: This paper explores aspects of early British atomic exhibitions by tracing the movement of a display model of Britain's first atomic pile (nuclear reactor) GLEEP. Following the model's journey through a variety of exhibitions aimed at different audiences—commercial fairs, displays staged for communities near the site of the new Windscale reactor, the national museum, and a Commonwealth exhibition—we can see how exhibition organisers adopted a variety of banalizing and obscuring tactics to promote the benign atom while maintaining secrecy over the wider atomic programme.